FACTORS AFFECTING THE TIMELINESS OF FINANCIAL STATEMENT SUBMISSION - Tanulia, Stephanie; Osesoga, Maria Stefani (Widya Mandala Surabaya Catholic University, 2022)
Research Purposes. This study aims to determine the effect of DER (debt to equity ratio), audit delay, public ownership structure, firm size, and auditor switching on the timeliness of financial statement submission. It is important in maintaining the relevance of information in financial statements because a relevant information can help users in making decision.Research Methods. Secondary data with a purposive sampling method was used in selecting samples and analyzed using logistic regression methods. There were 39 consumer goods companies used as samples after qualified the sample selection criteria.Research Result and Findings. The results conclude that DER, audit delay, and public ownership structure have a significant negative effect on timeliness of financial statements submission, firm size has a significant positive effect on the timeliness of financial statements submission, and auditor switching has no effect on the timeliness of financial statement submission.